2014
DOI: 10.1126/scisignal.2004824
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 Reinforces STAT3 Signaling and the Generation of Effector CD4 + T Cells by Promoting miR-124–Mediated Suppression of SOCS5

Abstract: Methyl CpG binding protein 2 (MeCP2) is an X-linked, multifunctional epigenetic regulator that is best known for its role in the neurological disorder Rett Syndrome; however, it is also linked to multiple autoimmune disorders. We examined a potential role for MeCP2 in regulating the responses of CD4+ T cells to stimulation with antigen. We showed that MeCP2 was indispensable for the differentiation of naïve CD4+ T cells into T helper type 1 (TH1) and TH17 cells and for TH1- or TH17-mediated pathologies in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 65 publications
(76 reference statements)
3
67
0
Order By: Relevance
“…This was a strong indication that the loss of MeCP2 in other T-cell subsets might compensate for Treg dysfunction and prevent the onset of overt autoimmunity. Indeed, we have examined the function of MeCP2 in effector T-cell lineages and found that MeCP2-deficient effector CD4 T cells are severely impaired in their production of inflammatory Th1 and Th17 cytokines (55). Nonetheless, it is clear that T-cell immunity is not normal in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…This was a strong indication that the loss of MeCP2 in other T-cell subsets might compensate for Treg dysfunction and prevent the onset of overt autoimmunity. Indeed, we have examined the function of MeCP2 in effector T-cell lineages and found that MeCP2-deficient effector CD4 T cells are severely impaired in their production of inflammatory Th1 and Th17 cytokines (55). Nonetheless, it is clear that T-cell immunity is not normal in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this from both our lab and others has been accumulating in recent years (Cronk et al, 2015a;Cronk et al, 2015b;Derecki et al, 2012;Horiuchi et al, 2016;Jiang et al, 2014;Jin et al, 2015;Li et al, 2014;Maezawa and Jin, 2010;O'Driscoll et al, 2013b;O'Driscoll et al, 2015). …”
Section: Figures and Tablesmentioning
confidence: 99%
“…It was previously shown by ourselves and others that MeCP2 plays an important role in immune cells, including T cells (Balmer et al, 2002;Jiang et al, 2014;Li et al, 2014;Yang et al, 2012) and myeloid cells (Cronk et al, 2015a;Derecki et al, 2012;Jin et al, 2015;Maezawa and Jin, 2010;O'Driscoll et al, 2013b;O'Driscoll et al, 2015), and thus it was hypothesized that chronic infections seen in MeCP2 (Yang et al, 2012). This defect in IFNγ production was hypothesized to account for the chronic infections seen in MeCP2 duplication syndrome (Yang et al, 2012 More recently, defects in antibody production have been implicated in MeCP2 overexpression.…”
Section: A In An Animal Model Of Mecp2 Overexpression Backgroundmentioning
confidence: 99%
See 2 more Smart Citations